The Properties of the Polaron in Semiconductor Quantum Dots Induced by Influence of Rashba Spin-Orbit Interaction (Journal of Atomic and Molecular Sciences, 2021)
The properties of the effective mass of polaron in semiconductor quantum dots by influence of Rashba spin-orbit (SO) interaction are studied. The relations of the strength of confinement $ω_0,$ the interaction energy and the effective mass of the polaron in the electron-LO phonon strong coupling region in a parabolic quantum dot on the vibration frequency is derived by using improved liner combination operator method. Numerical calculations for RbCl crystal are performed and the results show that the Rashba SO interaction makes the ground state energy and the effective mass of polaron split into two branches; the ground splitting energy and the effective mass will increase with the vibration frequency increasing. Whereas the interaction energy is sharply increased until the confinement strength reaches a certain value, then it will sharply decrease.
Keywords: semiconductor quantum dot; polaron; Rashba spin-orbit interaction; effective mass.